To look and listen in the city: political aspects of the vision and hearing in republic VIII and IX (Argos, 2017)
The Platonic conception of visual and auditory experiences on a double level (sensible and noetic) has an impact on his educational and political proposal, asexpressed in the Republic among other dialogues. A philological study of these semantic fields in Book VIII and the beginning of Book IX of the Republic allows us to postulate that in the Athenian's view changes in the forms of the polis are related to changes in human ways of seeing and hearing. Thus, this displacement may occur from deep to superficial sight and hearing, from unitary to multiple sight-hearing, or from seeing-hearing to not-seeing-hearing. In all these cases, this displacement has a correlate in a displacement of the ways the polis can be organized.
Keywords: Plato; Republic; Vision; Hearing; City